Nurses' Social Responsibility and its Relationship with Their Demographic Profiles - Zahra Marziyeh Hassanian; Amir Sadeghi; Ali Bagheri; Abbas Moghimbeighi (Hamadan University of Medical Sciences, 2017)
Introduction: Social responsibility is decision makers' commitment to actions that in addition to meeting their interests, provides and enhances well-being in the community. Demographic profiles effect social responsibility. The aim of this study was to determine the status of nurses' social responsibility and its relationship with their demographic profile. Methods: This study was a cross-sectional study, conducted in 2015. Using stratified proportional random sampling, 148 nurses were selected from educational and treatment centers of Hamadan University of Medical Sciences. The research instrument was a questionnaire with two parts including demographic and social responsibility. In this study, validity and reliability was confirmed and reliability was 0.86. Data analysis was performed using the SPSS software version 16. Ethical considerations were applied. Results: Based on the findings, 72.6% of nurses were at high level of total responsibility. The average of total responsibility was 7.3 ± 4.0. There was a significant relationship between nurses' social responsibility and their age and marital status (P < 0.05). There was no significant relationship between nurses' gender and education level, and their social responsibility. Conclusions: Since there was a relationship between social responsibility and the investigated features, it is necessary to consider demographic profiles in selection of nurses for crucial responsibilities at educational and treatment centers.